Investigation of the role of pedestal pressure and collisionality on type-I ELM divertor heat loads in DIII-D. (11th July 2018) - Knolker, M.; Bortolon, A.; Canal, G.P.; Evans, T.E.; Zohm, H.; Abrams, T.; Buttery, R.J.; Davis, E.M.; Groebner, R.J.; Hollmann, E.; Fenstermacher, M.E.; Lasnier, C.; et al.
Abstract: A non-dimensional collisionality scan conducted on DIII-D confirms a model for ELM energy densities recently put forward by Eich (2017 Nucl. Mater. Energy 12 84–90), but also reveals key effects that may explain the large scatter typically observed about the scaling. Electron cyclotron heating (ECH) close to the plasma edge was used to raise electron temperatures at the pedestal top and lower collisionality to ITER level, while the power of neutral beam injection (NBI) was decreased during discharges to operate closer to the L–H transition threshold. The scan reveals no explicit pedestal pressure dependence of the ELM energy densities. While collisionality does not play a decisive role, the ratio of heating power to the H-mode threshold power is identified as parameter determining the agreement with the model, with discharges marginally above the threshold showing the largest scatter in the database and exceeding the predicted ELM energy up to twofold. Operation close to the L–H-threshold is accompanied by low ELM frequency and large ELM heat loads. Using linear stability calculations, ELM energy densities are shown to scale inversely with to the most unstable linear mode number before the ELM crash. There are indications that the scatter in the data when compared with the Eich model prediction is caused by including only a limited set out of all quantities considered by linear stability analysis. While further ELM studies near the LH threshold are of great priority, the overall agreement of DIII-D with the Eich model recommends its use in extrapolations towards ITER.